B-cell activating factor and related genetic variants in lupus related atherosclerosis. (August 2018) - Theodorou, Evangelos; Nezos, Adrianos; Antypa, Eleni; Ioakeimidis, Dimitrios; Koutsilieris, Michael; Tektonidou, Maria; Moutsopoulos, Haralampos M.; Mavragani, Clio P.
Abstract: Background: Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease with an increased atherosclerotic risk compared to healthy population, partially explained by traditional cardiovascular (CV) risk factors. Recent data suggest B-cell activating factor (BAFF) as an important contributor in the pathogenesis of both SLE and atherosclerosis. The aim of the current study is to explore whether serum BAFF levels along with variants of the BAFF gene increase lupus related atherosclerotic risk. Patients-Methods: 250 SLE patients underwent assessment of plaque formation and/or intimal media thickness (IMT) measurements in carotid and femoral arteries by ultrasound. Disease related features and CV traditional risk factors were also assessed. Serum BAFF levels were determined by commercially available ELISA and five single nucleotide polymorphisms (SNPs) of the BAFF gene (rs1224141, rs12583006, rs9514828, rs1041569 and the rs9514827) were evaluated by PCR-based assays in all patients and 200 healthy controls (HC) of similar age and sex distribution. SLE patients were further divided in high and low BAFF groups on the basis of the upper quartile level of the distribution (1358 pg/ml). Genotype and haplotype frequencies in SLE patients and HC were determined by SNPStats and SHEsis software. Results: High-BAFF SLE group displayed increased rates of both plaque formation and arterial wall thickening (defined as IMT>0.90 mm) compared to patients with low BAFF levels (58.1% vs 43.6%, p:0.048 and 38.6% vs 23.2%, p-value: 0.024, respectively). The association remained significant after disease related features were taken into account (ORs [95%CI]: 2.2 [1.0–5.1] and 2.5 [1.1–5.5] for plaque formation and arterial wall thickening, respectively). Moreover, the presence of the AA genotype of the rs12583006 BAFF gene variant increased susceptibility for both lupus and lupus related plaque formation (ORs [95%CI]: 2.8 [1.1–7.1], and 4.4 [1.3–15.4] in the codominant model, respectively). Finally, the haplotype TTTAT was found to be protective for plaque formation among SLE patients (OR 0.3 [0.1–0.9]. No associations between BAFF gene variants with arterial wall thickening were detected. Conclusions: High BAFF serum levels in the upper 4th quartile as well as BAFF genetic variants seem to increase susceptibility for both lupus and lupus related subclinical atherosclerosis implying B-cell hyperactivity as a potential contributor in the pronounced lupus related atherosclerotic risk. Highlights: Independent association of high serum BAFF levels with subclinical atherosclerosis in lupus patients. AA genotype of the rs12583006 BAFF gene variant increases susceptibility for lupus related plaque formation. Protective role of the haplotype TTTAT against plaque formation among SLE patients.